Pertanggungjawaban Pemilik Hewan Ternak terhadap Kerusakan Lahan Warga di Desa Nobo Kabupaten Flores Timur - Maria Ivone Angelica Mukin; Darius Mauritsius; Helsina Fransiska Pello (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the Responsibility of Livestock Owners for Damage to Agricultural Land Owned by Residents in Nobo Village, Ile Boleng District, East Flores Regency. This study aims to determine the mechanism for resolving the problem of agricultural land damage caused by livestock in Nobo Village, Ile Boleng District, East Flores Regency and the form of accountability of livestock owners for damage to agricultural land caused by livestock. This study uses a qualitative research approach with an empirical research type. The techniques used in collecting data for this study are Observation, Interviews, Literature Studies, and Documentation. The results of this study indicate that the mechanism for resolving the problem of agricultural land damage caused by livestock in Nobo Village, Ile Boleng District, East Flores Regency through the stages of Reporting, Examination, and Trial. The law that regulates this, Article 1368 of the Civil Code, clearly regulates the responsibilities of livestock owners, and the Prohibition on releasing animals is also regulated in the Regional Regulation of East Flores Regency Number 25 of 1988 concerning Livestock Maintenance, but the sense of awareness of the community's obligations alone does not seem to be running. Claims that can be handed over to the pet owner who caused the loss can be in the form of compensation in the form of money and compensation in the form of returning it to its original condition (natural compensation).